Challenge-driven attention: interacting frontal and brainstem systems - Raizada, Rajeev D.; Poldrack, Russell A. (Frontiers in Human Neuroscience, 2008)
The world is an unpredictable place, presenting challenges that fl uctuate from moment to moment. However, the neural systems for responding to such challenges are far from fully understood. Using fMRI, we studied an audiovisual task in which the trials' diffi culty and onset times varied unpredictably. Two regions were found to increase their activation for challenging trials, with their activities strongly correlated: right frontal cortex and the brainstem. The frontal area matched regions found in previous human studies of cognitive control, and activated in a graded manner with increasing task diffi culty. The brainstem responded only to the most diffi cult trials, showing a phasic activity pattern paralleling locus coeruleus recordings in monkeys. These results reveal a bridge between animal and human studies, and suggest interacting roles for the brainstem and right frontal cortex: the brainstem may signal that an attentional challenge is occurring, while right frontal cortex allocates cognitive resources in response.